Penerapan Teori Belajar Behaviorisme dan Teori Belajar Sosial Bandura dalam Pembelajaran - Habsy, Bakhrudin All; Apriliya, Karina; Putri, Alifia Febriana; Aprilyana, Gian Salsabilla (Lembaga Yasin AlSys, 2024)
This research focuses on the Application of Behaviorism Learning Theory and Bandura's Social Learning Theory in Learning. The purpose of this research is to reveal behaviorism learning theory and Albert Bandura's social learning theory and implement them in learning. The content of behaviorism learning theory is that learning is a change in behavior as a result of the interaction between the stimulus as a result of the interaction between stimulus and response. The content of social learning theory emphasizes direct experience or observation, because according to Albert Bandura, namely people learn from what they read, hear, and see in the media, and also from other people and their environment. environment. The method used in the research is a qualitative method that intends to understand the object of research with sophisticated efforts through the art of speaking, the art of writing and the art of presenting what has been researched. In the study there are results, namely social learning theory Social learning theory helps understand the occurrence of aggression and psychological deviations and how to modify behavior. And the result of applying behavioristic theory and Bandura's social theory is the formation of a behavior that is aggression. This is the formation of a desired behavior. The desired behavior gets positive reinforcement and inappropriate behavior gets negative rewards and learner behavior. The learning behavior of students is the result of the ability of students to interpret knowledge or information, interpret a model that is not appropriate for them. information, interpret a model that is imitated, then process cognitively and determine actions according to the desired goals. determine the action according to the desired goal.